EFFECT OF WORK DISCIPLINE AND QUALITY SERVICES TO COMMUNITY SATISFACTION IN THE DEPARTMENT OF POPULATION AND CIVIL REGISTRATION OF BANDA ACEH CITY - Sutriani, Sutriani; Chalirafi, Chalirafi; Ristati, Ristati (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2022)
This research is very important to do because it is necessary to do an in-depth study by combining theoretical and field studies on the concepts of Work Discipline with the factors that affect Service Quality in order to create community satisfaction with the services provided by employees. The Population and Civil Registration Service is the implementing element of the Regional Government in the field of Population and Civil Registration which is led by the Head of the Service and is domiciled in the Region and is responsible to the Regent through the Regional secretary. Since a citizen is born until he dies, he will not be separated from administrative activities carried out by the Population and Civil Registration Service. So, it is proper for the Population and Civil Registration Service to provide good quality services to the community. The specific purpose of this study is to see how the influence of work discipline and service quality applied to community satisfaction. research analysis This type of research uses a combination of qualitative and quantitative approaches, known as mixed methodology. The technique used is a data collection technique with a questionnaire where the object of study in this study is the people who carry out administration at the Population and Civil Registration Office of Banda Aceh City. This study will explain the positive influence of work discipline and the quality of services provided on community satisfaction.